Analysis of herpesvirus infection and genome single nucleotide polymorphism risk factors in multiple sclerosis, Volga federal district, Russia - Lezhnyova, Vera; Davidyuk, Yuriy; Mullakhmetova, Asia; Markelova, Maria; Zakharov, Alexander; Khaiboullina, Svetlana; Martynova, Ekaterina (Frontiers in Immunology, 2022)
Multiple sclerosis (MS) is a heterogeneous disease where herpesvirus infection and genetic predisposition are identified as the most consistent risk factors. Serum and blood samples were collected from 151 MS and 70 controls and used to analyze circulating antibodies for, and DNA of, Epstein Barr virus (EBV), human cytomegalovirus (HCMV), human herpes virus 6 (HHV6), and varicella zoster virus (VZV). The frequency of selected single nucleotide polymorphisms (SNPs) in MS and controls were studied. Herpesvirus DNA in blood samples were analyzed using qPCR. Anti-herpesvirus antibodies were detected by ELISA. SNPs were analyzed by the allele-specific PCR. For statistical analysis, Fisher exact test, odds ratio and Kruskall–Wallis test were used; p<0.05 values were considered as significant. We have found an association between circulating anti-HHV6 antibodies and MS diagnosis. We also confirmed higher frequency of A and C alleles in rs2300747 and rs12044852 of CD58 gene and G allele in rs929230 of CD6 gene in MS as compared to controls. Fatigue symptom was linked to AC and AA genotype in rs12044852 of CD58 gene. An interesting observation was finding higher frequency of GG genotype in rs12722489 of IL2RA and T allele in rs1535045 of CD40 genes in patient having anti-HHV6 antibodies. A link was found between having anti-VZV antibodies in MS and CC genotype in rs1883832 of CD40 gene.